Ariel Dynamics
Sportwissenschaftliches Informationsangebot, das aus folgenden Teilen besteht: Introducing the Ariel Exercise System APAS Ariel Performance Analysis System About Ariel Dynamics Corporate Activities and Performances Articles and publications in scientific journals Articles and publications in the media about Gideon Ariel Comparison A Comparison of Commercially Available Systems Download APAS Download software products, patches and drivers History in progress Software manuals 3D Motion Database Optimization of Human Performance for All Ages Personal Gideon Ariel Presentations Product descriptions Miscellaneous projects using ADI products Services, Support and Online Library Sportsci Ariel CyberSport site and Mel Siff archives Independent studies conducted with APAS Tutorials and background information Database of video files in the media